Fueling Canadian AgTech: Support for Development and Commercialization - Instituto Interamericano de Cooperación para la Agricultura (IICA) (2025)
With the participation of Martin Vetter, Joanna Preston, Laura Mock, Al Schaefer and Darrell Petras